Transforming covalent organic framework into thin-film composite membranes for hydrocarbon recovery - Biswal, Bishnu P. (Separation Science and Technology, 2018)
We, for the first time, employed chemically stable covalent organic framework (COF) (TpPa-1) as a transport-active phase within the polymer (styrene-butadiene rubber; SBR) matrix to make TpPa-1@SBR thin-film composite (TFC) membranes. Three composite membranes, viz., TpPa-1(30)@SBR, TpPa-1(50)@SBR, and TpPa-1(70)@SBR have been prepared with varying COF content. These membranes were characterized for gas permeance and results were compared with the pristine SBR-based TFC membrane. The fully organic nature of chemically stable COF offered good compatibility with the host polymer matrix (SBR) and resulted into flexible TFC membranes even at 70% of COF loading; compared to the other porous material (MOFs or Inorganic fillers), it is appreciable.
Keywords: Covalent organic framework; hydrocarbon recovery; propylene–propane; styrene-butadiene rubber; thin film composite

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).

ZIF-8@DBzPBI-BuI composite membranes for olefin/paraffin separation - Kunjattu, Shebeeb H.; Ashok, Varsha; Bhaskar, Anand; Pandare, Kiran; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
ZIF-8 is a member of Zeolitic Imidazole Framework family having high internal surface area, the high thermo-chemical stability and ease of synthesis gained immense attention for its highly selective sieving ability. Transforming it into a membrane form and practical utility remains a challenge. Any success towards this direction would radically reduce the cost of propylene/propane separation. Present study reports use of substituted polybenzimidazole (DBzPBI-BuI) for fabrication of flexible, thus scalable composite membranes with ZIF-8 (ZIF8@DBzPBI-BuI) possessing host-guest compatibility. The membrane with 30% ZIF-8 loading showed promising propylene-propane separation (ideal selectivity of 32.7), coupled with propylene permeability of 12.13 Barrer. Analysis of sorption shed light on the high contribution of diffusivity on governing permeation properties of the composite membranes. The mixed gas analysis offered highly encouraging results in comparison to known composite membranes of different polymers with ZIF-8. Placement of present data on `upper-bound' showed a rapid enhancement in selectivity by the addition of ZIF-8 in the polymer matrix, which seems to be a result of the elimination of inter-phase defects. It was made possible due to the functionality of host polymer.
Keywords: Gas permeation; Olefin/paraffin separation; Polybenzimidazole (PBI); ZIF-8

Nanoparticle size-fractionation through self-standing porous covalent organic framework films - Dey, Kaushik; Kunjattu, Shebeeb H.; Chahande, Anurag M.; Banerjee, Rahul (Angewandte Chemie-International Edition, 2020)
Covalent organic frameworks (COFs) have attracted attention due to their ordered pores leading to important industrial applications like storage and separation. Combined with their modular synthesis and pore engineering, COFs could become ideal candidates for nanoseparations. However, the fabrication of these microcrystalline powders as continuous, crack-free, robust films remains a challenge. Herein, we report a simple, slow annealing strategy to construct centimeter-scale COF films (Tp-Azo and Tp-TTA) with micrometer thickness. The as-synthesized films are porous (SA(BET)=2033 m(2) g(-1) for Tp-Azo) and chemically stable. These COFs have distinct size cut-offs (ca. 2.7 and ca. 1.6 nm for Tp-Azo and Tp-TTA, respectively), which allow the size-selective separation of gold nanoparticles. Unlike, other conventional membranes, the durable structure of the COF films allow for excellent recyclability (up to 4 consecutive cycles) and easy recovery of the gold nanoparticles from the solution.
Keywords: covalent organic frameworks; films; nanofilter; Nanoparticles; size-selective separation

Composites of HKUST-1@nanocellulose for gas-separation and dye-sorption applications - Muhamed, Shamna; Sunny, Blesson; Kunjattu, Shebeeb H.; Alagarsamy, Thirumurugan (CHEMISTRY-A EUROPEAN JOURNAL, 2023)
In this study, composites of HKUST-1 MOF with nanocellulose, HKUST-1@NCs, have been prepared and explored for CO2/N-2 gas-separation and dye-sorption based applications. Our biopolymer-MOF composites are prepared via a copper ion pre-seeding method, in which, the HKUST-1 crystallites are grown in situ on the Cu-seeded and carboxylate anchored NC fibers for a better interfacial integration between the MOF and the polymer matrices. Static gas sorption studies show the capability of one of our HKUST-1@NC composites to reach similar to 300 % enhancement in the CO2/N-2 sorption selectivity compared to the corresponding MOF alone - blank reference sample prepared at similar conditions. The same composite, C100, in the bulk powder form, shows a remarkable IAST sorption selectivity of 298 (CO2/N-2) at 298 K and 1 bar for the CO2/N-2 (15/85, v/v) gas mixture. The relative position of the C100, in the bound plot visualizations of the CO2/N-2 separation trade-off factors indicate a significant potential. The HKUST-1@NC composites have also been processed along with a polymeric cellulose acetate (CA) matrix as HKUST-1@NC@CA films to study them as free-standing mixed-matrix membranes. The CO2/N-2 sorption selectivity, at 298 K and 1 bar is 600 for one such membrane, C-120@CA, as bulk sample studied by the static gas sorption. The composite, C120, exhibits a good uptake with an enhancement of 11 % for alizarin and 70 % for Congo red in comparison to the uptakes of the corresponding blank reference HKUST-1 sample, B120.
Keywords: CO2 separation; dye sorption; MOFs; nanocellulose composites; sustainable polymers

Scalable, interfacially synthesized, covalent-organic framework (COF)-based thin-film composite (TFC) hollow fiber membranes for organic solvent nanofiltration (OSN) - Kunjattu, Shebeeb H.; Thorat, Nitin M.; Gawas, Saroj; Kharul, Ulhas K. (ACS Applied Materials and Interfaces, 2024)
Covalent organic frameworks have great potential for energy-efficient molecular sieving-based separation. However, it remains challenging to implement COFs as an alternative membrane material due to the lack of a scalable and cost-effective fabrication mechanism. This work depicts a new method for fabricating a scalable in situ COF hollow fiber (HF) membrane by an interfacial polymerization (IP) approach at room temperature. The 2D COF film was constructed on a polyacrylonitrile HF substrate using aldehyde (1,3,5-trimethylphloroglucinol, Tp) and amine (4,4 `-azodianiline (Azo) and 4,4 `,4 `'-(1,3,5-triazine- 2,4,6-triyl) trianiline (Tta)) as precursors. The COF membrane on the PAN substrate showed 99% rejection of Direct red-80 with remarkable solvent permeance. The rejection analysis revealed that the structural aspects of the solute molecule play a major role in rejection rather than the molecular weight. We further optimized the precursor concentrations to improve the permeation performance of the resulting membrane. The durability study reveals excellent stability of the membrane toward organic solvents. This study also demonstrated the easy scalability of the membrane fabrication approach. The approach was further extrapolated to fabricate a cation-based COF membrane. These charged membranes exhibited an enhanced rejection performance. Finally, this approach can facilitate industrially challenging molecular sieving applications using COF-based membranes.
Keywords: covalent-organic framework; hollow fiber; interfacial polymerization; organic solvent nanofiltration; selective COF membrane